A simple surgical technique for correcting malunion after midshaft clavicle fracture. (August 2021) - van Essen, Tom; Hillen, Robert Jan
Clavicle malunion occurs in two-thirds of all clavicle fractures treated conservatively. It can lead to pain, shoulder dysfunction and cosmetic complaints. Surgical treatment of all midshaft fractures will lead to overtreatment, as not all malunions are symptomatic. In the past, several treatment modalities for correcting malunion of the clavicle have been described, and all have been successful but none have shown superiority. This article describes a new surgical technique with excising a wedge to realign the clavicle malunion.